INTEGRATED RISK PICTURE METHODOLOGY FOR AIR TRAFFIC MANAGEMENT IN EUROPE - Kharchenko, Volodymyr; Chynchenko, Yuriy (Proceedings of National Aviation University, 2013)
The article deals with the analysis of the researches conducted in field of the Integrated risk picture methodology. Benefits of the concept, operational documentation and potential users of Integrated risk picture methodology have been reviewed. Principles of implementation and impact on Air Traffic Management have been analysed and general recommendations applicable for Ukrainian aeronautical system have been proposed.